Island myocutaneous medial gastrocnemius flap in the reconstruction of knee and proximal lower leg defects - Radovanović, Drakče (Medicinski časopis, 2018)
Skin defects with bare bones, cartilage and ligaments in the knee region are a significant surgical problem. The aim of this study is to present a reconstruction of the compound skin and soft tissue defects at the knee region with an island arterial medial myocutaneous gastrocnemius flap.